Shifting social norms to prevent age-disparate transactional sex in Tanzania: what we can learn from intervention development research - Howard-Merrill, Lottie; Zimmerman, Cathy; Sono, Revocatus; Riber, John; Wamoyi, Joyce; Pawlak, Piotr; Rolleri Insignares, Lori; Yaker, Robyn; Buller, Ana Maria (Frontiers in Psychology, 2023)
This paper reflects on the development process (2015-2020) of the Learning Initiative on Norms, Exploitation, and Abuse (LINEA) Intervention. The LINEA Intervention is a multi-component social norms intervention to prevent age-disparate transactional sex in Tanzania. This paper aims to: 1) critically reflect on the LINEA Intervention development process by retrospectively comparing it with a pragmatic, phased framework for intervention development in public health, the Six Essential Steps for Quality Intervention Development (6SQuiD); and 2) discuss the usefulness and applicability of this framework to guide intervention development for gender-based violence prevention. This paper contributes to a growing field of intervention development research to improve the designs of interventions to prevent gender-based violence. Findings showed that the LINEA Intervention development approach mostly aligned with the steps in 6SQuID framework. However, the LINEA Intervention development process placed particular emphasis on two phases of the 6SQuID framework. First, the LINEA Intervention development process included significant investment in formative research, feasibility testing, and refinement; and second, the LINEA Intervention was informed by a clearly articulated behavior change theory – social norms theory. Beyond the 6SQuID framework, the LINEA Intervention development process: i) followed a non-linear, iterative process; ii) applied ongoing feasibility testing to refine the intervention, and iii3) relied on co-development with local implementers and participants. This paper suggests future components for a robust intervention development process, highlighting beneficial additions to the 6SQuID approach, a well-recognised intervention development sequence. Particularly useful additions include incorporating sufficient time, flexibility and resources to foster meaningful collaborations and iteration on the intervention design.